Glomerulonefrites nos pacientes espondiloartríticos - Daniela Castelo Azevedo (2010)
Introdution: The spondyloarthopathies are a interrelated group of diseases but that have clinical, epidemiological, anatomic, pathologic, immunogenetic and radiologic features that distinguish them from each other. Medical literature has mentioned an increased frequency of kidney diseases in spondiloarthritic patient, such as amyloidosis, anti-inflammatory nephropathy and IgA glomerulonephritis. Nevertheless, there is not a formal recommendation to investigate renal manifestations in this population. Objective: The aim of this study was to determine glomerulonephritis prevalence in spondiloarthritic patients (SA) attending in a Rheumatology Service, and evaluate clinical variables associated with. Patients and methods: Sociodemographic characteristics, spondiloarthritis type, time since diagnosis and disease activity, nonsteroidal anti-inflammatory drugs use, 7 HLA- B27 positivity, blood levels of creatinin and urea, main comorbidities, hematuria and proteinuria were investigated in all patients. Those with hematuria were subsequently evaluated for the presence dysmorphic urinary red cells and those with proteinuria, with 24-hour urine protein measure. Kidney biopsy was performed on those with glomerular hematuria and/or proteinuria above 3,5g/24-hour. Results: Microscopic hematuria was the most frequent abnormality found in urinary analysis (44, 7%). Eight patients (10, 5%) were suspected to have glomerular hematuria. Four in five patients submitted by kidney biopsy were diagnosed with IgA nephropathy and one with thin-basement membrane disease. There was no statistical association between hematuria and chronic kidney disease, systemic arterial hypertension, proteinuria, high levels of creatinin, spondiloarthritis type and disease activity. Conclusions: Periodic urine analysis of SA patients must be a routine recommendation. Nephritis definitive diagnosis is extremely relevant, owing to implications in the spondiloarthritis treatment and the patients prognosis.